Recent trends in the translation industry in Slovenia - Fišer, Darja (The Journal of Specialised Translation, 2008)
Following two earlier studies, which examined the use of translation tools and the needs of the translation job market, this paper reports on the results of an empirical study into the state of affairs in the Slovene translation industry. A survey of the Slovene translation market was performed to analyse the demand for translation services, how translation businesses are organised and what technology they use. The second part of the paper compares the working environments of ten most successful translation companies. Finally, a custom-built project management system that helps one of the fastest-growing translation companies with its workflow was examined.